IMPROVING STUDENTS’ READING COMPREHENSION THROUGH IINTERACTIVE READ-ALOUD TECHNIQUE - Edi Santoso (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
Abstract:The present study, entitled Improving Students’ Reading Comprehension throughInteractive Read-Aloud, attempts to unlock problems found in teaching and readingcomprehension through interactive read-aloud in a Senior High School of Sport (SMAN Olah Raga) Lampung, in Metro. The findings revealed that students’ readingcomprehension improved through interactive read-aloud. The improvement can be seenfrom the increase of test results, meaning construction, and motivation. The process ofreading activities showed that the teacher’s gesture and body language, 20 questions,explain and guess activities were proven to help the students construct meaning from thegiven texts. In addition, interactive read-aloud is effective to boost students’ motivationto comprehend the texts. Key words: Reading comprehension, interactive read-aloud.